Global Infectious Diseases in March 2023: Monthly Analysis - Taihan Li; Yi Luo; Jiazhen Zou; Yufan Wu; Yinfu Sun; Qi Xiang; Minjing He; Shuqiong Zhang; Dongliang Liu; Guodan Li; Wenjin Yu; Qun Su; et al. (Zoonoses)
Infectious diseases pose a major burden on public health and economic stability among societies worldwide. For centuries, they have been among the leading causes of death and disability, and are currently presenting growing challenges to health security and human progress. This report focuses on global outbreaks of infectious diseases, relying on Shusi Tech’s Global Epidemic Information Monitoring System to systematically summarize outbreak timing and location in infected populations from February 24, 2023, to March 23, 2023. Therefore, surveillance of infectious diseases on a continental scale is important to assess, recognize and protect against the risks that these diseases may pose to animal, domestic animal and human health on a global scale.